Central Limit Theorems For Multicolor Urns With Dominated Colors - Patrizia Berti; Irene Crimaldi; Luca Pratelli; Pietro Rigo (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2009)
An urn contains balls of d >= 2 colors. At each time n >= 1, a ball is drawn and then replaced together with a random number of balls of the same color. Let An =diag (An,1, . . . ,An,d) be the n-th reinforce matrix. Assuming EAn,j = EAn,1 for all n and j, a few CLTs are available for such urns. In real problems, however, it is more reasonable to assume EAn,j = EAn,1 whenever n >= 1 and 1 <= j <= d0, liminf EAn,1 > limsup EAn,j whenever j > d0, for some integer 1 <= d0 <= d. Under this condition, the usual weak limit theorems may fail, but it is still possible to prove CLTs for some slightly different random quantities. These random quantities are obtained neglecting dominated colors, i.e., colors from d0 + 1 to d, and allow the same inference on the urn structure. The sequence (An : n >= 1) is independent but need not be identically distributed. Some statistical applications are given as well.
Keywords: 330; Central limit theorem; Clinical trials; Random probability measure; Stable convergence; Urn model